2010
DOI: 10.3791/1951
|View full text |Cite
|
Sign up to set email alerts
|

Mouse Models of Periventricular Leukomalacia

Abstract: We describe a protocol for establishing mouse models of periventricular leukomalacia (PVL). PVL is the predominant form of brain injury in premature infants and the most common antecedent of cerebral palsy. PVL is characterized by periventricular white matter damage with prominent oligodendroglial injury. Hypoxia/ischemia with or without systemic infection/inflammation are the primary causes of PVL. We use P6 mice to create models of neonatal brain injury by the induction of hypoxia/ischemia with or without sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 2 publications
1
23
0
Order By: Relevance
“…These MRI studies performed in heterogeneous groups of preterm children used different quantitative methodologies and reported cortical and subcortical GM volume decreases in infancy (1,17,18), childhood (19,20), or adolescence (21). Thalamic damage is also a common finding in PVL neuropathological studies (2,8), as well as MRI studies (6,7) and PVL mouse models (22). Moreover, quantitation of neuronal loss in a PVL postmortem study showed that the most affected GM structure was the thalamus, with a 38% loss that surpassed the 21% found in the cerebral cortex (2).…”
Section: Discussionmentioning
confidence: 99%
“…These MRI studies performed in heterogeneous groups of preterm children used different quantitative methodologies and reported cortical and subcortical GM volume decreases in infancy (1,17,18), childhood (19,20), or adolescence (21). Thalamic damage is also a common finding in PVL neuropathological studies (2,8), as well as MRI studies (6,7) and PVL mouse models (22). Moreover, quantitation of neuronal loss in a PVL postmortem study showed that the most affected GM structure was the thalamus, with a 38% loss that surpassed the 21% found in the cerebral cortex (2).…”
Section: Discussionmentioning
confidence: 99%
“…The etiology behind brain lesions in preterm infants is multifactorial and partly unknown but most likely includes infection/inflammation, hyperoxia, hypoxia, ischemia, excitotoxicity and injury secondary to IVH/PVH (Favrais et al, 2011; Hagberg et al, 2002; Volpe 2009b). In order to model HI in animals corresponding to the human at preterm, the Rice‐Vannucci model has been adapted to younger animals including PND 5 (Albertsson et al, 2014), PND 6 (Shen et al, 2010) and PND 7 mice as well as PND 3 rats (Sizonenko et al, 2003).…”
Section: Introductionmentioning
confidence: 99%
“…To facilitate survival of transplanted cells, we induced insults in P6 Rag1 −/− immunodeficient mice using unilateral carotid ligation followed with hypoxia, which resulted in selective injury to the subcortical white matter, without detectable injury to cortical neurons (Liu et al, 2011a; Shen et al, 2010). Consistent with our previous studies (Liu et al, 2011a; Shen et al, 2010), we observed reactive astrogliosis at 4 days after induction of PVL injury selectively in the ipsilateral side of the brain (Fig. S4A–C).…”
Section: Resultsmentioning
confidence: 99%
“…5A). Immature hiPSC-Astros were grafted to the periventricular area adjacent to the corpus callosum (CC) where hypo-myelination was observed (Liu et al, 2011a; Shen et al, 2010) (Fig. 5B).…”
Section: Resultsmentioning
confidence: 99%